2016
DOI: 10.1073/pnas.1513565113
|View full text |Cite
|
Sign up to set email alerts
|

Slip-mediated dewetting of polymer microdroplets

Abstract: Classical hydrodynamic models predict that infinite work is required to move a three-phase contact line, defined here as the line where a liquid/vapor interface intersects a solid surface. Assuming a slip boundary condition, in which the liquid slides against the solid, such an unphysical prediction is avoided. In this article, we present the results of experiments in which a contact line moves and where slip is a dominating and controllable factor. Spherical cap-shaped polystyrene microdroplets, with nonequil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…The nonsphericity of the droplet increases when the slip length is first decreased from the full slip limit. Further decreasing the slip length, we observe a new feature with respect to previous works (McGraw et al 2016): the non-sphericity reaches a maximum and then starts to decrease. This behavior is demonstrated for different equilibrium contact angles.…”
Section: Introductionsupporting
confidence: 48%
See 2 more Smart Citations
“…The nonsphericity of the droplet increases when the slip length is first decreased from the full slip limit. Further decreasing the slip length, we observe a new feature with respect to previous works (McGraw et al 2016): the non-sphericity reaches a maximum and then starts to decrease. This behavior is demonstrated for different equilibrium contact angles.…”
Section: Introductionsupporting
confidence: 48%
“…In this article, by extending the theoretical work of McGraw et al (2016), we elucidate the transition between the quasistatic and non-quasistatic evolutions of a dewetting droplet. We study the dewetting of a viscous droplet for a wide range of slip lengths and various equilibrium contact angles using the boundary element method.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Spreading of droplets in the partial-wetting regime can therefore serve as an alternative test for the height-dependence of surface tension; we have shown that our new model allows investigations of the spreading process without the need for precursor films (Pahlavan et al 2015). Visualization of the contactline motion at micro/nano-scales (Chen et al 2014;Qian et al 2015;McGraw et al 2016;Deng et al 2016) could therefore lead the way in refining and validating models for interfacial flows.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one might expect that, all other things equal, dewetting will occur more quickly as the film repellency of the solid is increased, for instance, by increasing θ e . Indeed, the first studies of dewetting reported a typical dewetting speed U / θ 3 e 4 , and subsequent experimental and theoretical studies of dewetting in the presence of a gas phase have either verified or assumed this result [5][6][7][8][9][10][11][12] .…”
mentioning
confidence: 99%